Walking the road to freedom : a story about Sojourner Truth - Ferris, Jeri.; Hanson, Peter E. (Minneapolis : Carolrhoda Books, 1988)
Traces the life of the Black woman orator who spoke out against slavery throughout New England and the Midwest.
Children's Catalog (Wilson)
Booklist
5.7
3-6
Keywords: Truth, Sojourner, -- d. 1883 -- Juvenile literature; Truth, Sojourner, -- d. 1883.; Truth, Sojourner, d. 1883.; Afro-Americans -- Biography -- Juvenile literature; Abolitionists -- United States -- Biography -- Juvenile literature; Social reformers -- United States -- Biography -- Juvenile literature; Afro-Americans -- Biography; Abolitionists; Reformers; Blacks -- Biography; Abolitionists -- Biography; Reformers -- Biography